Upaya Pengendalian Dan Pencegahan Hipertensi Melalui Pendidikan Kesehatan Dalam Pengaturan Pola Hidup Sehat - winnellia fridina sandy rangkuti; Sudarto; Sarliana Zaini; Ajeng Puspita Putri (WASATHON Jurnal Pengabdian Masyarakat, 2023)
Hypertension in Indonesia occupies the second position of the ten most outpatient diseases with a prevalence of 34% measured in people over the age of 18 years in 34 provinces of Indonesia in 2018 (Rikesdas, 2018). Hypertension can be caused by diet, high sodium consumption and lack of physical activity. This often occurs in people living in urban and coastal areas. Where people often consume sodium that is quite high with less activity habits in urban communities. The purpose of this activity is to provide education about hypertension. The method of this activity is by conducting tests (pre test and post test), before and after counseling is carried out to assess the level of public knowledge or understanding of hypertension as an indicator of the success of a health promotion program. Counseling showed that there was an increase in public knowledge or understanding about hypertension, from 30 to 97 percent. Based on the results of this assessment, it is hoped that the public can better understand the control and be aware of hypertension.